Analisis Penyerapan Gas Karbondioksida (CO2) Dengan Larutan NaOH Terhadap Kualitas Biogas Kotoran Sapi - Mara, Made (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2012)
The rising costs for the fossil fuel based energy and concern over the environment have caused a resurgence of interest in anaerobic treatment and subsequent use of the biogas produced during the treatment of organic waste as fuel.  Biogas from cattle dung has become a potential renewable energy source for both domestic and commercial usage especially in Lombok. Unfortunetly, due to the presence of carbon dioxide (CO2) and Hydrogen sulphide (H2S) in biogas, it has become extremely difficult to store and transport it effectively and has lower energy density.This paper presents the study in biogas purification by mean of absorbing the CO2 gas using the NaOH solution. In addition, the biogas production process used in 3 (three) kinds of cattle dung from horses dung, cows dung and buffaloes dung by the composition of 1 kg of manure to 1 Liter of water.                 The results show that generated the largest volume on the composition of C with average volume reached 72.419 liters, then the composition B reached 61.794 liters, and the lowest in the composition of A with an average volume of 51.478 liters. The highest power generated in the treatment composition A with 2.5 N NaOH solution at 108.5 watts and the lowest power generated by the composition of C without treatment of 25.67 Watts.